Building Community in Adult Education Graduate Programs - Shannon K. Deer; Jill Zarestky; Catherine A. Cherrstrom (Adult Education Research Conference, 2013)
The purpose of this paper is to discuss the opportunities and challenges of launching a graduate student seminar series in order to build community and informationsharing networks. We share successful program strategies and findings based on experience and a mixed methods study.